PUBLIC GOOD AND PUBLIC INTEREST IN THE PROCESS OF UKRAINIAN STATE-MAKING - Зайдель, М.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
Specific of state-making in the context of independent Ukrainian state-building is examined. It is focused on the essential content of concepts of „public good” and „public interest”. Two traditions of understanding of „public” concept by H.Arendt and J.Habermas are underlined. It is concentrated on the problem of formation of public sphere, definition of „public good” and „public interest” according to the process of state-making  in Ukraine.